Violence Against Doctors: Kerala High Court Refused Pre-Arrest Bail of Accused: A Case Study (Indian Internet Journal of Forensic Medicine and Toxicology, 2022)
The definition of the word ‘violence’ in the statute is clearly indicative of the purpose behind the Act. The preamble to the aforementioned Act states that it is enacted to prohibit violence against healthcare service persons and to prevent damage and loss to property in healthcare service institutions. Petitioner is alleged to have wrongfully restrained a doctor (the defacto complainant) on 12.04.2022 and threatened her while she was on her way from the doctor’s room to the casualty of the hospital, thereby causing obstruction to her official duty and committing the offences under sections 341, 353 and 506 of the Indian Penal Code, 1860 (for short ‘the IPC’) and section 3 and 4(1) of the Healthcare Act. The petitioner vehemently contended that petitioner is innocent of the allegations and that he had not committed any of the offences alleged. It was further contended that as per the FIR, no injury or assault had taken place, and hence the allegation constitutes only a minor offence, petitioner ought to be released on pre arrest bail. Learned Public Prosecutor on the other hand submitted that, though the offences under the IPC are bailable, the provisions under the Healthcare Act, are non-bailable and that granting pre-arrest bail to the petitioner would prevent the custodial interrogation, which is essential in the peculiar circumstances. Kerala High Court concluded that bearing in mind the objective of the Act, if pre-arrest bail is granted to the petitioner, a wrong message will also be sent to the public. Reckoning the nature and gravity of the offence committed by the petitioner, High Court is not inclined to exercise the discretion of granting pre-arrest bail to the petitioner. There is need to create awareness among patient community about the purpose of the Healthcare Act and its impact on perpetrator of violence against doctors and damage to property is not good for society and ultimately looser would be themselves.
Keywords: Violence; Offence; Pre-arrest bail; Bailable offence; Non-bailable offence